Challenges Faced by English Teachers during Limited Face-to-Face Meetings at Junior High Schools in Semanu and the Solutions - Nugraha, Damar; Sari, Mariska (Universitas Muhammadiyah Yogyakarta, 2022)
The government has implemented Community Activities Restrictions Enforcement (CARE) to avoid the spread of the COVID-19 pandemic. Following the vaccination program from the government, the level of CARE in Yogyakarta Special Region has decreased. This achievement has provided opportunities for schools to implement limited face-to-face meetings. Schools that have decided to implement face-to-face meetings are required to follow certain learning policies and health protocols. This research aimed to explore the challenges faced by English teachers in the Semanu area during limited face-to-face meetings and the solutions. The research employed a descriptive qualitative research design with interviews as the data collection method. After gathering data from five English teachers from two junior high schools in Semanu as participants, the researchers processed the data in several steps, namely transcribing the data, member checking, and coding the process. The research results show that the challenges faced by English teachers come from three factors. The first factors are facilities, in that students and teachers have problems with their gadgets and the internet connection. The second factor is students' behaviours in that during the limited face-to-face meeting, the students showed various behavioural problems such as cheating, low activity in online learning, and dishonesty. The last factor is 30 minutes duration face-to-face meeting policy which made the face-to-face meeting is not effective. English teachers have several solutions to help them overcome these challenges, and the solutions are conducting home visits; inviting students to come to school; creating learning recaps; simplifying and reducing the difficulty level of students’ assignments; and creating printed forms of assignments and learning materials as alternative methods.